Understanding the Growth of African Financial Markets - Andrianaivo, Mihasonirina (IMF Working Papers; Working Paper ;, 2009)
This paper examines empirically the determinants of financial market development in Africa with an emphasis on banking systems and stock markets. The results show that income level, creditor rights protection, financial repression, and political risk are the main determinants of banking sector development in Africa, and that stock market liquidity, domestic savings, banking sector development, and political risk are the main determinants of stock market development. We also find that liberalizing the capital account promotes financial market development only in countries with high incomes, well- developed institutions, or both. The powerful impacts of political risk on both banking sector and stock market development suggest that resolution of political risk may be important to the development of African financial markets.